1992
DOI: 10.3758/bf03199665
|View full text |Cite
|
Sign up to set email alerts
|

Remembering emotional events

Abstract: Recent experiments have implied that emotional arousal causes a narrowing of attention and, therefore, impoverished memory encoding. In contrast, other studies have found that emotional arousal enhances memory for all aspects of an event. We report two experiments investigating whether these differing results are due to the different retention intervals employed in past studies or to their different categorization schemes for the to-be-remembered material. Our results indicate a small role for retention interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

32
326
9
15

Year Published

1997
1997
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 401 publications
(382 citation statements)
references
References 46 publications
32
326
9
15
Order By: Relevance
“…The false recognition sentences, unlike in other studies where distracters are easier to distinguish (e.g. Burke et al, 1992;Heuer and Reisberg, 1990), included contents that ®t in well with the event and, as in studies analysing the misinformation e ect (e.g. Loftus and Ho man, 1989;Weingardt et al, 1994), subjects could have been misled by suggested information.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…The false recognition sentences, unlike in other studies where distracters are easier to distinguish (e.g. Burke et al, 1992;Heuer and Reisberg, 1990), included contents that ®t in well with the event and, as in studies analysing the misinformation e ect (e.g. Loftus and Ho man, 1989;Weingardt et al, 1994), subjects could have been misled by suggested information.…”
Section: Discussionmentioning
confidence: 81%
“…First, in spite of great e orts made for subjects to be incidental observers of the emotional material (e.g. Burke et al, 1992;Christianson, 1984;Heuer and Reisberg, 1990), there was nothing which contrasted in a direct and simple fashion the di erences between incidental and intentional processing. Second, by using a ®lm instead of static materials, such as slides, the di erence between the type of information (central and peripheral) and evaluated contents (actions and details) was systematically distinguished, thereby analysing the e ect of both variables in two successive recall tests, recognition and response con®dence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations